2011
DOI: 10.1038/nrmicro2615
|View full text |Cite
|
Sign up to set email alerts
|

Hfq and its constellation of RNA

Abstract: Hfq is an RNA-binding protein that is common to diverse bacterial lineages and has key roles in the control of gene expression. By facilitating the pairing of small RNAs with their target mRNAs, Hfq affects the translation and turnover rates of specific transcripts and contributes to complex post-transcriptional networks. These functions of Hfq can be attributed to its ring-like oligomeric architecture, which presents two non-equivalent binding surfaces that are capable of multiple interactions with RNA molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
1,023
2
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 943 publications
(1,056 citation statements)
references
References 158 publications
(244 reference statements)
19
1,023
2
12
Order By: Relevance
“…Typically regulation is mediated by base-pairing between the so-called seed region of the sRNA and critical sites in the mRNA target -in the classical scenario the ribosome binding site, thereby preventing translation initiation and inducing mRNA decay. For this to occur, many sRNAs rely on a chaperone protein, referred to as Hfq (host factor of the RNA bacteriophage Qβ) (Vogel and Luisi, 2011). Hfq facilitates inter-molecular RNA-RNA interactions, recruits specific ribonucleases for target mRNA degradation and protects the bound sRNA from being nucleolytically attacked, thereby increasing its stability (Wagner, 2013).…”
Section: Bacterial Srnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically regulation is mediated by base-pairing between the so-called seed region of the sRNA and critical sites in the mRNA target -in the classical scenario the ribosome binding site, thereby preventing translation initiation and inducing mRNA decay. For this to occur, many sRNAs rely on a chaperone protein, referred to as Hfq (host factor of the RNA bacteriophage Qβ) (Vogel and Luisi, 2011). Hfq facilitates inter-molecular RNA-RNA interactions, recruits specific ribonucleases for target mRNA degradation and protects the bound sRNA from being nucleolytically attacked, thereby increasing its stability (Wagner, 2013).…”
Section: Bacterial Srnasmentioning
confidence: 99%
“…Since STnc440 associates with Hfq Sittka et al, 2008), it is likely to regulate mRNAs by base pairing (Vogel and Luisi, 2011). Thus, in order to identify direct targets of this sRNA, a previously described pulse-expression approach was applied (Masse et al, 2005;Papenfort et al, 2006).…”
Section: Pulse-expression Experiments Identify Stnc440 Targetsmentioning
confidence: 99%
“…However, it has been shown that other RNA-binding proteins, e.g. the welldocumented Hfq, have a role in the regulation of the expression of genes involved in virulence (Brennan & Link, 2007;Chao & Vogel, 2010; Christiansen et al, 2004;Vogel & Luisi, 2011). Of note, enterococci and streptococci do not harbour hfq-like genes (Sun et al, 2002).…”
mentioning
confidence: 99%
“…Hfq is known as the central mediator of sRNA-based gene regulation in bacteria as it establishes dynamic interactions of a wide range of RNA molecules and manipulates translation and degradation of many mRNAs important for pathogenesis (Chao and Vogel 2010;Vogel and Luisi 2011). In fact, hfq knock-out derivatives of many important pathogens (e.g.…”
Section: Regulatory and Sensory Rnasmentioning
confidence: 99%